The Enigma of Capital and The Crises of Capitalism - Harvey, David (London; Profile Books, 2011)
The author exposes the essence of capitalism as self-interest, as opposed to responsible and humane; and periodic meltdowns are not only inevitable but essential to its survival.
English
Keywords: Capitalism- Decline; HB501 Economic Theory. Demography- Capital. Capitalism-